Review Artikel: Penggunaan Metode Kualitatif dalam Penelitian Telefarmasi - Fara Mutia Bimantika; Mahacita Andanalusia; Azizatul Adni; Silhiyatun Mayada; Lalu M. Rifqi Azami S (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The application of qualitative approaches in healthcare research, especially within the pharmaceutical field, continues to grow. One area where these methods are increasingly utilized is telepharmacy research, which requires deeper exploration to better understand the perceptions and experiences of both patients and healthcare providers. This article aims to present an overview of qualitative methods that can serve as a foundation for future studies. The study employed a literature review design using a narrative approach, analyzing 12 selected articles that met predefined inclusion and exclusion criteria. The findings revealed a diversity in research designs and data collection techniques, highlighting the adaptability of qualitative methods in capturing respondents’ perspectives and experiences in telepharmacy settings. Additionally, several studies reported the use of qualitative data analysis software to facilitate the coding process. In conclusion, the most commonly applied approach was exploratory qualitative research, often utilizing semi-structured interviews and focus group discussions (FGDs). The collected data were primarily analyzed using thematic analysis, supported by software such as NVivo, MAXQDA, ATLAS.ti, and Microsoft Excel.